-7(2x-3)+7=-14x+28

Simple and best practice solution for -7(2x-3)+7=-14x+28 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(2x-3)+7=-14x+28 equation:


Simplifying
-7(2x + -3) + 7 = -14x + 28

Reorder the terms:
-7(-3 + 2x) + 7 = -14x + 28
(-3 * -7 + 2x * -7) + 7 = -14x + 28
(21 + -14x) + 7 = -14x + 28

Reorder the terms:
21 + 7 + -14x = -14x + 28

Combine like terms: 21 + 7 = 28
28 + -14x = -14x + 28

Reorder the terms:
28 + -14x = 28 + -14x

Add '-28' to each side of the equation.
28 + -28 + -14x = 28 + -28 + -14x

Combine like terms: 28 + -28 = 0
0 + -14x = 28 + -28 + -14x
-14x = 28 + -28 + -14x

Combine like terms: 28 + -28 = 0
-14x = 0 + -14x
-14x = -14x

Add '14x' to each side of the equation.
-14x + 14x = -14x + 14x

Combine like terms: -14x + 14x = 0
0 = -14x + 14x

Combine like terms: -14x + 14x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| y=81-(9-2x)(9-2x) | | 2x-3=2(x-6) | | 1.8x=4.8 | | 3x-21+1=x | | 0.12(y-3)+0.14y=0.06y-0.01(70) | | 4x+2=x | | 5p=6+4p | | 4z+0.375=5z+0.125 | | 4x-10y-1z=-51 | | 9-4(4-(7y-6))= | | -6x-20y+1z=-63 | | z^7+9z^6=0 | | (x+(2-i))(x-(2-i))=0 | | 0.20x+0.45(50)=29.5 | | 9(2y-6)-(5y+3)= | | 6r^7+6r^5=0r^6+9r^4 | | (20-2x)*(40-2x)*x=x | | (v+3)(v-4)=v | | (4x+16)= | | 3(2k+4)-13k+4+2= | | 4.8x-8.4y-4.5=0 | | 0.007(x+3)=0.008x+0.0018 | | -3k+5k-5+2k= | | -.1x+2.1y=-9.7 | | 17y-73=y-4 | | 13r+s+20r+11s= | | 0.9z=13z | | -2(x-7)+7=21 | | (0)b=1 | | 17(y-73)=y-4 | | y=x^3+x^2-16x-16 | | 50x-60= |

Equations solver categories